L’inexistence du travail en RDC - BAISOMBI BWANYE Eugène,; BARUANI DESIRE, (IJRDO - Journal of Social Science and Humanities Research, 2020)
As a maximum value in theworld in general and in DR. Congo inparticular, the work remains andremains an ultimate goal, for theCongolese nation to take off, whichhas been locked up  for a decade inhigh unemployment. We thereforerationally call on the Congolesegovernments to make a strong appealto the Western experts to helprehabilitate the various companies inthe DRC in order to proclaim itsprosperity in all national facets.